Introduction of infection control module for undergraduate medical students: experience at a rural medical college in India. - Singh, Suman Praveen; Modi, Chirag; Patel, Chirag; Shah, Purvi (International Journal of Infection Control, 2014)
Health care associated infections are preventable by following Infection Control protocols which are not taught to medical student. Poor state of knowledge and practices in medical students about infection control has been shown in various studies. “Patient Safety Module” by WHO strongly recommends incorporation of infection control module in curriculum of medical schools as, the future doctors need to understand these concepts at an early stage to be able to incorporate them in practice. We designed and implemented such a module to improve the knowledge, skills and attitude of medical students towards infection control practices through a formal teaching program.This educational intervention of four and half hours, was designed and implemented for students in their final phase of medical education. The module focused on standard precautions, sterilization and disinfection, spillage, biomedical waste management and sharp injury. Student’s feedback was taken immediately as well as after a year in the form of anonymous structured questionnaire along with the written assessment in the form of multiple choice questions. Descriptive analysis of the responses was done.The module was rated as excellent by more than 95% (n=90) of the students. The topics included were perceived of immediate importance, usefulness & relevance by all the students. Majority of the students felt that such session must be conducted at regular interval particularly during internship when they can have direct application of the infection control practices. Thus, inclusion of infection control module in undergraduate medical curriculum is strongly recommended by the authors.Keywords: Teaching, infection control, undergraduate medical students